ARITHMETIC OF p‐IRREGULAR MODULAR FORMS: FAMILIES AND p‐ADIC L‐FUNCTIONS. Issue 4 (10th September 2021) - Betina, Adel; Williams, Chris
Abstract: Let f new be a classical newform of weight ≥2 and prime to p level. We study the arithmetic of f new and its unique p ‐stabilisation f when f new is p ‐irregular, that is, when its Hecke polynomial at p admits a single repeated root. In particular, we study p ‐adic weight families through f and its base‐change to an imaginary quadratic field F where p splits, and prove that the respective eigencurves are both Gorenstein at f . We use this to construct a two‐variable p ‐adic L ‐function over a Coleman family through f, and a three‐variable p ‐adic L ‐function over the base‐change of this family to F . We relate the two‐ and three‐variable p ‐adic L ‐functions via p ‐adic Artin formalism. These results are used in work of Xin Wan to prove the Iwasawa Main Conjecture in this case. In an appendix, we prove results towards Hida duality for modular symbols, constructing a pairing between Hecke algebras and families of overconvergent modular symbols and proving that it is non‐degenerate locally around any cusp form. This allows us to control the sizes of (classical and Bianchi) Hecke algebras in families.